Fokus areas vir 'n bestuursinligtingstelsel vir top-, middel- en laervlakbestuur in 'n finansiële instelling - P. J.S. Bruwer; D. Van Der Walt (South African Journal of Business Management, 1992)
Focus areas for a management information system for top, middle and lower level management in a financial institution. This research project was conducted at one of South Africa's major banks. This bank has a client base of approximately five million clients and approximately eight million active accounts. Since the term 'Management Information Systems' was relatively new to this bank, the purpose of this project was to do a critical evaluation of the existing management information system. This was done by means of a questionnaire to top, middle and lower level management in the bank. These data were processed by making use of stepwise linear regression as well as all possible subset multiple linear regression methods. A number of critical success factors were identified and prioritized for each of four subsets of the population. These subsets are the following: top and middle management; regions; operational management; and all users of the information system. A number of recommendations were made for establishing an improved service provided by the systems development team.
Keywords: 650